Facile Synthesis of Novel V0.13Mo0.87O2.935 Nanowires With High-Rate Supercapacitive Performance - Jiang, Haishun; Sun, Wenjing; Li, Wenyao; Wang, Zhe; Zhou, Xiying; Wu, Zexing; Bai, Jinbo (Frontiers in Chemistry, 2019)
Binary metal oxides composed of molybdenum-vanadium oxides are anticipated to have a promising potential for supercapacitors. Here we are reporting the synthesis of one-dimensional V0.13Mo0.87O2.935 nanowires through a facile one-step hydrothermal method. This nanowire presented high specific capacitance of 394.6 F g-1 (1 mV s-1) as an electrode applied to the supercapacitor. Importantly, this electrode showed a perfect rate capability of 91.5% (2 to 10 A g-1), the continuous verified outstanding cyclic voltammetry with 97.6% after 10000 cycles. These superior electrochemical properties make the synthesized V0.13Mo0.87O2.935 nanowires a prospective candidate for high-performance supercapacitors.